2020
DOI: 10.1007/s40544-020-0432-x
|View full text |Cite
|
Sign up to set email alerts
|

Nanofriction characteristics of h-BN with electric field induced electrostatic interaction

Abstract: The nanofriction properties of hexagonal boron nitride (h-BN) are vital for its application as a substrate for graphene devices and solid lubricants in micro- and nano-electromechanical devices. In this work, the nanofriction characteristics of h-BN on Si/SiO2 substrates with a bias voltage are explored using a conductive atomic force microscopy (AFM) tip sliding on the h-BN surface under different substrate bias voltages. The results show that the nanofriction on h-BN increases with an increase in the applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…18 As a 2D crystal material, hexagonal boron nitride (BN) possesses many exceptional features, such as high thermal conductivity, high surface to volume ratio, 15 limited crystal defects, 19 and chemical stability. 20 Similar to graphene, 21 BN consists of a 2D superposition of honeycomb structures, characterized by strong chemical bonds within layers and weak van der Waals forces between layers, 22 suggesting that intrinsic BN is immune to adsorption of gas molecules. Nevertheless, a number of experimental and theoretical 23–26 studies have shown that BN surface activity could be effectively promoted by doping of chemical heteroatoms.…”
Section: Introductionmentioning
confidence: 99%
“…18 As a 2D crystal material, hexagonal boron nitride (BN) possesses many exceptional features, such as high thermal conductivity, high surface to volume ratio, 15 limited crystal defects, 19 and chemical stability. 20 Similar to graphene, 21 BN consists of a 2D superposition of honeycomb structures, characterized by strong chemical bonds within layers and weak van der Waals forces between layers, 22 suggesting that intrinsic BN is immune to adsorption of gas molecules. Nevertheless, a number of experimental and theoretical 23–26 studies have shown that BN surface activity could be effectively promoted by doping of chemical heteroatoms.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Notably, 2D materials enable the realization of near-frictionless sliding contacts via a mechanism known as structural superlubricity. 8,9 Its practical interest spurred vibrant research 10−13 in an attempt to tune/control structural superlubricity either extrinsically (e.g., by strain 14 and electric fields 15 ) or intrinsically (e.g., by graphene fluorination 16 ). The first approach, despite offering the advantage of controlling friction via an external knob, suffers from various practical issues.…”
mentioning
confidence: 99%
“…Understanding and controlling friction is arguably one of the oldest quests of mankind. , From the great pyramids of Giza to car engines and all the way down to microelectromechanical devices, a detailed control of this ubiquitous phenomenon closely followed our technological advancement. In this regard, two-dimensional (2D) materials are no exception because aside from their remarkable electronic and optical properties, they possess extraordinary tribological properties. , Notably, 2D materials enable the realization of near-frictionless sliding contacts via a mechanism known as structural superlubricity. , Its practical interest spurred vibrant research in an attempt to tune/control structural superlubricity either extrinsically (e.g., by strain and electric fields) or intrinsically (e.g., by graphene fluorination). The first approach, despite offering the advantage of controlling friction via an external knob, suffers from various practical issues.…”
mentioning
confidence: 99%
“…A basic understanding is that a local puckering caused by out-of-plane deformation needs more external force to assist in the forward sliding, while the thicker layers caused less puckering because of the higher bending stiffness. It is also undeniable that chemical vapor deposition (CVD)-grown monolayer h -BN in micrometer-sized domains could provide low friction, accompanied by oxidation and electric resistance. , In addition, due to the electron transfer caused by the nature of ionic covalent h -BN compounds, the contact stress, substrate temperature, and electric field play a significant role in the nanoscale friction behavior. ,, For example, the ionic characteristics of h -BN result in a higher barrier energy compared with graphene, where the increased temperature in the friction process would be related to thermal excitation to overcome the high energy barrier and encourage slipping . However, a scientific understanding of the external conditions inducing friction behavior and the correlation among mechanical property, thermal conductivity, and friction performance in thin h -BN remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 In addition, due to the electron transfer caused by the nature of ionic covalent h-BN compounds, the contact stress, substrate temperature, and electric field play a significant role in the nanoscale friction behavior. 9,24,25 For example, the ionic characteristics of h-BN result in a higher barrier energy compared with graphene, where the increased temperature in the friction process would be related to thermal excitation to overcome the high energy barrier and encourage slipping. 26 However, a scientific understanding of the external conditions inducing friction behavior and the correlation among mechanical property, thermal conductivity, and friction performance in thin h-BN remain elusive.…”
Section: Introductionmentioning
confidence: 99%